ASEAN COMMUNITY: A STUDY OF FAMILIARITY AMONG YOUTHS IN KUCHING, SARAWAK - Mohd Razali, Othman (Universiti Malaysia Sarawak (UNIMAS), 2022)
Association of Southeast Asian Nations (ASEAN) is a political and economic union of ten member states in Southeast Asia. The organisation promotes intergovernmental cooperation and facilitates economic, political, security, military, educational and sociocultural integration between its members and countries in Asia-Pacific (ASEAN, 2020). This study provides an overview on the familiarity towards ASEAN and the initiative of ASEAN Community among youths in Kuching, Sarawak. This study also identifies the factors affecting the level of familiarity towards ASEAN and the initiative of ASEAN Community among youths in Kuching, Sarawak. The result of this study was analysed from the responses provided by the youths in Kuching, Sarawak. This study employs quantitative method in the data collection by using questionnaires to obtain information from the respondents. Overall, this study aims were to identify the level of familiarity towards ASEAN and the initiative of ASEAN Community among youths in Kuching, Sarawak. This study also aims to identify the factors affecting the level of familiarity towards ASEAN and the initiative of ASEAN Community among youths in Kuching, Sarawak.